Comparative Analysis of Differentially Mutated Genes in Non-Muscle and Muscle-Invasive Bladder Cancer in the Chinese Population by Whole Exome Sequencing - Wang, Fangming; Dong, Xiying; Yang, Feiya; Xing, Nianzeng (Frontiers in Genetics, 2022)
Objective: To characterize the spectra of mutations in non–muscle invasive bladder cancer (NMIBC) and muscle-invasive bladder cancer (MIBC) in the Chinese population to identify any mutational features and find potential therapeutic targets. Materials and methods: We collected fresh bladder tumor samples from NMIBC (n=9) and MIBC patients (n=11) along with adjacent normal bladder tissue specimen and peripheral blood sample. Using whole exome sequencing (WES), we analyzed the mutation spectra of those NMIBC and MIBC bladder cancer (BCa) specimen. Results: Our results demonstrated that 95% of BCa patients (19/20) had varying degrees of driver gene mutations, FGFR3 (45%), KMT2D (40%), PIK3CA (35%), ARID1A (20%), EP300 (20%), KDM6A (20%), KMT2C (20%), and STAG2 (20%) were the most frequently mutated genes in BCa patients. NMIBC and MIBC exhibited different genomic alterations. FGFR3 (67%), PIK3CA (56%), and RHOB (44%) were the most frequently mutated genes in NMIBC patients. Of note, RHOB mutation only occurred in NMIBC, whereas mutations of KMT2D (55%), TP53 (36%) and KMT2B (27%) were frequently detected in MIBC, and TP53 and KMT2B mutation only occurred in MIBC. The frequency of mutations in DNA damage repair (DDR) gene was higher in MIBC than that in NMIBC (91% vs. 78%, 6.2 vs. 2.4 gene mutations per patient). Copy number alterations (CNAs) occurred at more diverse chromosomal locations in NMIBC, but the CNA burden was higher in MIBC (9.01 [2.07-31.51] vs 4.98 [0.99-9.73] mutations/Mb)., the trend of which was consistent with the tumor mutation burden (TMB) (8.26 [4.63-21.84] vs 5.58 [3.87-9.58] mutations/Mb). Among the current set of single-base substitution (SBS) signatures including SBS 1, 2, 5, 13, and 40, we identified one differently expressed signature between NMIBC and MIBC patients: SBS 13 (APOBEC related) was more evident in MIBC than NMIBC (p=0.025). Conclusions: There were different gene mutational characteristics and signatures between NMIBC and MIBC in the Chinese population. Frequency of DDR, CNA burden and TMB were higher in MIBC. Our analysis revealed that several genes in NMIBC did not overlap with those reported in MIBC, suggesting that a fraction of NMIBC and MIBC likely developed secondary to different precursor lesions.